NATURAL SCIENCES MODULE BASED ON SCIENTIFIC APPROACHES FOR INTERACTION OF LIVING THINGS TOPIC TO IMPROVE COGNITIVE ACCOMPLISHMENT OF 8th GRADERS JUNIOR HIGH SCHOOL - Imega Syahlita Dewi; Widha Sunarno; Sri Dwiastuti (Jurnal Pendidikan Sains, 2017)
Abstract: This research is a development research (R&D) which aims at identifying the feasibility and effectiveness of Natural Sciences Module based on scientific approaches for Interaction of Living Things topic. It employed pre-experimental design with One-Shot Case Study. The module developed is a printed module employing Four-D model adapted from Thiagarajan (1974). The module consists of three learning activities and it is systematically presented using scientific approaches (observing, questioning, trying, associating, and communicating) to improve 7th Graders’ cognitive accomplishment. The results show that students’ cognitive accomplishment in Learning Activity I was 80%, Learning Activity II was 83.34%, and Learning Activity III was 96.64%. It means that students’ have achieved Minimum Mastery Criteria. It can be concluded that the developed module is feasible to be used in learning to improve students’ cognitive accomplishment. Key Words: module, scientific, cognitive accomplishment, learning outcome, pre-experimental designAbstrak: Penelitian ini merupakan penelitian pengembangan (R & D) yang bertujuan untuk mengidentifikasi kelayakan dan efektivitas Modul Ilmu Pengetahuan Alam berdasarkan pendekatan ilmiah untuk topik Interaksi Makhluk Hidup dengan lingkungannya. Penelitian ini menggunakan desain pra-eksperimental dengan One-Shot Case Study. Modul yang dikembangkan adalah modul cetak yang menggunakan model Four-D diadaptasi dari Thiagarajan (1974). Modul ini terdiri dari tiga kegiatan pembelajaran dan disajikan secara sistematis dengan menggunakan pendekatan ilmiah (mengamati, mempertanyakan, mencoba, mengasosiasi, dan mengkomunikasikan) untuk meningkatkan hasil belajar kognitif siswa ke-las VII SMP. Hasil penelitian ini menunjukkan bahwa hasil belajar kognitif siswa dalam Aktivitas Pembelajaran I adalah 80%, Aktivitas Pembelajaran II adalah 83,34%, dan Aktivitas Pembelajaran III adalah 96,64%. Artinya, siswa telah mencapai Kriteria Ketuntasan Minimum. Dapat disimpulkan bahwa modul yang dikembangkan layak untuk digunakan dalam pembelajaran untuk meningkatkan hasil belajar kognitif siswa.Kata kunci: modul, saintifik, capaian kognitif, hasil belajar, desain pre-experimental